PENGARUH FASILITAS KERJA, PENGAWASAN, IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BADUNG - Rupadana, I Gede Eka; Widnyani, Ida Ayu Putu Sri; Dewi, Nyoman Diah Utari (LPPM Institut Pendidikan Nusantara Global, 2023)
A government agency in achieving its goals, it is necessary to have elements that support the operation of the organization. One of the elements that support the success of these goals is humans who are the most valuable and most important resource in the organizational environment. This study aims to determine and analyze the effect of work facilities, supervision and organizational climate on the performance of Civil Servants at the Secretariat of the Regional House of Representatives of Badung Regency. The number of respondents involved in this study was 90 people using the survey method. Data collection using a Likert scale questionnaire. Data analysis techniques using SPSS. The results showed that partially work facilities, supervision, organizational climate had a positive and significant effect on the performance of Civil Servants at the Secretariat of the Regional House of Representatives of Badung Regency. Simultaneously work facilities, supervision and organizational climate have a positive and significant effect on the performance of civil servants at the Secretariat of the Regional House of Representatives of Badung Regency. The magnitude of the effect of work facilities, supervision, organizational climate simultaneously on employee performance is 74.4 percent. It is expected that employees improve their skills at work so that performance increases.